Investigation of cutting temperature and cutting force from mist flow pattern in MQL technique - Dorairaju, Hemarani (2015)
Minimum Quantity Lubrication (MQL) is an alternative method to supply the cutting fluid in the formation of mist. MQL has proven to reduce machining cost and increase machining performance. Previous research have stated that machining performance is affected by the lubricant type, flow rate, the distance between nozzle and tool tip, and the workpiece material. These important parameters are not reported in many research documents. MQL is known for its many benefits but no one was able to prove that the statement is true or ever suggested a systematic procedure to prove MQL’s efficiency. The effectiveness and the working principle of MQL are still questionable with very few explanations provided. The present study is about investigation of cutting temperature and cutting force from mist flow pattern in MQL technique The MQL nozzle distance and cutting fluid flow pattern are among the factors that can provide optimum machining performance in term of cutting force and cutting temperature. The objective of this study is to conduct machining process using MQL technique with different combination of spray parameters and to optimize spray parameters for minimum machining temperature and cutting forces. The four nozzle distances of 3, 6, 7 and 9 mm were selected based on the results obtained from Phase Doppler Anemometry (PDA). The machining performance was evaluated under three levels of cutting speed and two levels of feed rate at constant depth of cut. The cutting force was measured using a set of dynamometer and cutting temperature using thermal imager. The most suitable mist flow pattern during machining was the largest spray cone angle supplied under 0.4 MPa input air pressure. The results obtained from the machining process shows a significant reduction of cutting force and cutting temperature at the nozzle distance in the range of 6 to 9 mm under 0.4 MPa input air pressure for larger diameter OD30 nozzle.